Kehidupan Ekonomi Penambang Kapur Bukit Tui Kota Padang Panjang Pasca Galodo Tahun 1987 - 1998 - Mia Aprilia; Rusdi Rusdi (Jurusan Sejarah FIS UNP, 2023)
This research discusses the changes in the economic livelihoods of limestone miners in Bukit Tui from 1987 to 1998. The focus of this study is on the economic impact experienced by limestone miners in Bukit Tui after the Galodo disaster in 1987. The purpose of this research is to understand the life of limestone miners in Bukit Tui after the Galodo disaster in 1987 and to find out the efforts made by the miners to meet their needs from 1987 to 1998. This study is a qualitative research using historical methods such as heuristic steps, source criticism, interpretation, and historiography. The results of this research reveal that the Galodo disaster significantly changed the lives of limestone miners. The economic impact felt by the miners after the Galodo disaster was the loss of their livelihoods, which then led to a decline in the economy. The limestone miners then made various efforts to meet their economic needs, such as finding new jobs as traders, motorcycle taxi drivers, farmers, and so on.